Blood Pressure and Sodium Consumption: A Study of Fast Food Workers in Central Jakarta - Lestari, Adni Ageng; Razaq, Asa Azkatu; Soekatri, Moesijanti Y.E. (Poltekkes Kemenkes Palu, 2024)
This study aimed to investigate the relationship between blood pressure and the frequency of consuming sodium-rich foods among employees of a western-style fast food restaurant